Dovecots: tourist attraction of Isfahan villages - Ansari, Atefeh; Heydari Bani, Dariyush (Pure and Applied Science Advances, 2014)
Today, tourism is considered as one of the major economicactivities in many courtiers. Given the financial resources devoted to and the workforce involved in tourism, it has appeared as a global thriving industry.One of the notable subdivisions of this industry is rural tourism. This kind oftourism has played a considerable role in attracting tourists and in helpingeconomic activities all around the world. Iran is no exception. In this regard,among the cities of Iran, villages of Isfahan have a good potential for ruraltourism. Also, considering the existing problems in Isfahan villages such aswater shortage for irrigation, low agricultural productivity and joblessnessetc, rural tourism may be a reliable economic alternative. Of the oldstructures survived in Isfahan villages, dovecots are especially important.Varity in form and size, fascination of the indoor space as well as harmonywith surrounding nature are among the main rural attractions of the dovecotsfor tourists. Unfortunately, some of the dovecots are disappearing or havebecome deserted. In this connection, the studies so far done on dovecots havemainly examined architectural features of the dovecots as historicalstructures; little attention has been paid to the visual character of them asrural landscapes and tourism attractions. In the present study, afterconducting field observations, collecting and processing data, the conditionsof villages with dovecots were analyzed. Accordingly, 18 villages- based on 11criteria- were compared with each other and then ranked. The villages enjoyingbetter facilities, better accessibility, more dovecots and cultural, historicaland natural attractions were ranked higher. Thus, higher rank villages can beconsidered as potential tourism centers locally and regionally.